Peran Bahasa Indonesia dalam Penyampaian Dakwah di Lingkungan Masjid Al-Asy’ari Unisba - Muhammad Rendi (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Da'wah comes from the Arabic language,” دعا, يدعو, دعوة” which means "to call" or "to invite." Da'wah itself is an activity carried out by Muslims to spread the teachings of Islam to others. This activity aims to invite others to understand, accept, and practice Islamic teachings in their daily lives. Da'wah can be conducted through various means, such as lectures, sermons, religious studies, discussions, and via social media or written materials. In delivering da'wah in the environment of Al-Asy'ari Mosque at Universitas Islam Bandung (Unisba), the role of Indonesian language as the national language has a strategic role in conveying effective and widely accepted da'wah messages within the campus community. Through a qualitative descriptive approach, this research was conducted through media observations and the distribution of questionnaires to students. The role of Indonesian language in delivering da'wah at Al-Asy'ari Mosque is evident as its usage is prevalent in every event, such as sermons, lectures, studies, and more. Indonesian language also serves as a tool to facilitate communication among students from diverse backgrounds and as an effective medium for conveying da'wah messages.